(untitled) (The International Journal of Educational Sciences and Arts, 2026)
This study aims to analyze the transformations introduced by generative artificial intelligence into patterns of media disinformation within the digital environment of Saudi Arabia, and to examine their implications for digital credibility in terms of information accuracy, source independence, and public trust. The study is grounded in a central research problem: the growing ability of generative models to produce hyper-realistic textual and visual content, including fake news, deepfakes, and algorithmically targeted messages. Such developments have made it increasingly difficult to distinguish between truth and fabrication, posing unprecedented professional, ethical, and epistemic challenges for media institutions and digital audiences. The study adopts a media survey method within a descriptive-analytical framework, using a questionnaire as the main tool for collecting quantitative data from a representative sample of social media users in Saudi Arabia. The proposed sample size consists of 384 respondents, determined according to the Krejcie and Morgan formula. The study focuses on measuring users’ exposure to forms of automated disinformation, assessing the impact of generative AI on the dimensions of digital credibility, and exploring users’ perceptions of verification practices and information literacy in confronting synthetic media manipulation. The significance of this study lies in its contribution to bridging a research gap in Arabic and Saudi media scholarship concerning the relationship between generative AI and media disinformation. It also provides an analytical framework that may assist media institutions and policymakers in understanding the risks of synthetic disinformation and in developing technological and awareness-based strategies to strengthen digital credibility and protect the Saudi media space in alignment with national digital transformation and Saudi Vision 2030.